THREE SPOT GOURAMI (Trichogaster trichopterus) FOOD HABITS IN THE KOMERING RIVER'S DOWNSTREAM, SOUTH SUMATERA - Ridho, Moh. Rasyid; Patriono, Enggar; Junaidi, Endri; Avesena, Muhammad; Karolina, Anita; Ardelia, Vera (BIOVALENTIA: Biological Research Journal, 2021)
One of the downstream areas of the Komering River with potential for capture fisheries is Sungai Dua Village. One of the types of fish caught by fishermen in Sungai Dua is the three spot gourami (Trichogaster trichopterus). The three spot gourami fish is a type of freshwater consumption fish that has high economic value. But the fishes only rely on catches from nature. If the fishing is carried out continuously, without domestication and cultivation, it will cause a decline in the fish population. The research about the biological aspects of red-eye septic fish (Trichogaster trichopterus) which include food habits, relationship length and weight, condition factors and stomach fullness index. This research was conducted from April to June 2017. Sampling was carried out in the downstream waters of the Komering River in Sungai Dua Village, Banyuasin Regency, South Sumatra. Fish samples were analyzed at the Animal Taxonomy Laboratory, Department of Biology, Faculty of Mathematics and Science, Sriwijaya University. The determination of stations in sampling was carried out using multiple sampling methods, namely purposive sampling and quota sampling. The result of this research showed that (1) the Cyanophyta is the main food for the three spot gourami, Diatomae and Desmidiacae as a complementary food, while the additional foods are Rhizopoda, Chlorophyta, Ostracoda, and Entomostraca, (2) The growth pattern of red-eyed fish is negative allometric with a b value of -2 (b <3), the increase in length is faster than the weight gain, (3) The highest condition factor value is found in the size range 6.01-7.00 cm of 23.25 gr / cm and the lowest condition factor value is in the size range 5.01-6.00 cm of 0.62 gr / cm, and (4) The highest hull fullness index value of the red eye sepat fish hull is in the size range 7.01-8.00 cm at 32.86% and the lowest hull fullness index value at the size range 8.01-9.00 cm is 2.05% .